The Application of Fuzzy Logic for Quality Assessment of Fresh Milk - Santoso, Imam; Wijana, Susinggih; Pratiwi, Widya Hari (Jurnal Teknologi Pertanian, 2010)
The quality assessment of raw material fresh milk in PT XXX was carried out organoleptically, physico-chemically, and microbiologically.  The assessment included some variables and determinations of parameter as main problem. The aims of this study were to determine quality parameter for assessing with fuzzy logic to increase accuracy of fresh milk quality. The analytical method used was Fuzzy Inference System Mamdani with Matlab program. The stage was carried out such as: variable appointment and forming of fuzzy set, appointment of membership function, appointment of fuzzy rule, and defuzzyfication to get the output in the form of numeral of domain of fuzzy set.  As a result, quality assessment of fresh milk with fuzzy logic consisted of 6 variables, were color, taste, odor, pH, protein, and the resazurin.  The range of this quality assessment was 1-9, that 9 was the highest value.  The result of analysis with fuzzy logic showed that the best defuzzyfication method was MOM (Mean of Maximum). Parameter of quality assessment with fuzzy logic for accepted fresh milk was 5.5 to 9, and below that value fresh milk will be rejected or returned to supplier.Keywords: fuzzy logic, quality assessment, fresh milk